Long-term follow-up of unoperated, nonscissoring spiral metacarpal fractures. Issue 4 (December 2014) - Macdonald, Brittany B; Higgins, Amanda; Kean, Susan; Smith, Carolyn; Lalonde, Donald H
Background: Spiral metacarpal fractures can result in shortening of the metacarpal shaft, which may lead to extension lag at the metacarpophalangeal joint and reduced grip strength. These fractures have been surgically treated to restore metacarpal length; however, there are complications associated with surgery, postoperative management and wound healing, which further threaten power recovery in the hand. Objective: To determine the effect of conservative management of unoperated, nonscissoring spiral metacarpal fractures. Methods: Sixty-one consecutive patients presenting with nonscissoring spiral metacarpal fractures were treated nonoperatively and studied prospectively to determine the natural history of their power outcome. Thumb fractures and those requiring surgical intervention for scissoring were excluded. Results: Follow-up data of a minimum of five months (mean follow-up 87 weeks) were available for 13 patients. Mean grip strength at final follow-up was 36.18 kg on the uninjured side and 36.58 kg on the injured side. The strength-difference values did not differ significantly from zero (P=0.72). Conclusion: The loss of metacarpal length associated with these fractures may not cause a power deficit sufficiently large to significantly affect grip strength and functional recovery in the hand. A prospective randomized controlled trial of operated versus unoperated, nonscissoring metacarpal fractures is warranted.